PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Indriani, Novia; Subaida, Ida; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2024)
Transportation Companies are one of the factors related to the development and economic development of countries worldwide. Transportation companies are among the most important companies and are the largest contributors to national development, resulting in the country's economy increasing along with the rise of increasingly sophisticated technology. This study aimed to determine the effect of profitability and leverage on firm value with dividend policy as a moderating variable in transportation companies listed on the IDX in 2019-2022. The population of this study were all transportation companies listed on the IDX in 2019-2022, as many as 45 companies, with samples taken from 9 companies. The sampling technique used a nonprobability sampling technique with a purposive sampling technique. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart 3.0 application show that Profitability has a significant positive effect on Firm value, Leverage has a positive but insignificant impact on Firm value, Dividend policy negatively but insignificantly weakens the role of Profitability in increasing Firm value, then Dividend policy negatively but insignificantly weakens Leverage on Firm value.